2017
DOI: 10.1080/10641963.2017.1377218
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension regulating angiotensin peptides in the pathobiology of cardiovascular disease

Abstract: Renin angiotensin system (RAS) is an endogenous hormone system involved in the control of blood pressure and fluid volume. Dysregulation of RAS has a pathological role in causing cardiovascular diseases through hypertension. Among several key components of RAS, angiotensin peptides, varying in amino acid length and biological function, have important roles in preventing or promoting hypertension, cardiovascular diseases, stroke, vascular remodeling etc. These peptides are generated by the metabolism of inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 83 publications
0
29
0
2
Order By: Relevance
“…In the same way, Ang II is a hormone involved in the pathophysiology of hypertension and atherosclerosis, which also exerts its effects through PKC [31,32]. In fact, Ang II is an activator of NOX5 in human microvascular endothelial cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, Ang II is a hormone involved in the pathophysiology of hypertension and atherosclerosis, which also exerts its effects through PKC [31,32]. In fact, Ang II is an activator of NOX5 in human microvascular endothelial cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the year 1898, Tigerstedt and Bergman discovered renin to be the rate-limiting enzyme and the first recognized component of RAS [1]. At first, the RAS was thought to be a sequence of many enzymatic steps, eventually producing a single bioactive metabolite, Angiotensin II (AngII) [2,13]. However, in recent years, the identification of novel enzymes and receptors has magnified the classical view of the RAS [14,15].…”
Section: A Brief Overview Of Rasmentioning
confidence: 99%
“…AngII is considered to be the finical production of the classic RAS [2,13]. It has a direct role in the cardiovascular, damage of the glucose transport system [3], and insulin resistance [80].…”
Section: Angii and Ampkmentioning
confidence: 99%
“…In the present study, we found four differentially expressed endogenous peptides derived from PKD1 mapped to the functional domains of this protein (Table 2). It is known that cleavage of precursor proteins by proteases generates peptides that may gain specialized functions not ascribed to their precursors, which could reflect the state of a cell under certain physiological conditions or pathological processes [36]. Therefore, it is reasonable to believe that although the functions of these PKD1-derived peptides may not have a strong association with their precursor protein, these peptides may play an important role in the early prediction of GDM.…”
Section: Discussionmentioning
confidence: 98%